Hermeneutika dalam Tafsir al-Qur’an: Sinergitas Instrumen Penafsiran al-Qur’an Dunia Islam dan Barat - A. Komarudin (At-Ta'wil: Jurnal Pengkajian al-Qur'an dan at-Turats, 2019)
Hermeneutics acceptance as one of the methods of interpretation of the Qur'an is still a discourse among Muslim intellectuals, both pro and contra. Some who accept the presence of hermeneutics assume that hermeneutics is one of the most relevant methods used to understand the Qur'an, even though hermeneutics is a western product. Hermeneutics is needed in terms of understanding the Qur'an, especially contemporary problems that have not been resolved in classical interpretations. Whereas those who refuse to be a priori and expressly reject hermeneutics are used as methodologies even when compared with Islamic interpretation. Reinforced again that hermeneutics is a western prodak which was originally used for biblical interpretations which differed in characteristics from the Qur'an. Then there are some Muslim intellectuals who try not to oppose and do not support carelessly, as long as hermeneutics is still in the realm of an understanding methodology that is not equated with the science of interpretation which is patience, then it can be accepted. This study seeks to direct discusses that occur among Muslim intellectuals by presenting the reasons for each group in descriptions and trying to compromise the middle ground as an effort to synergize the interpretation of the science of interpretation (Islam) and the west. So that we can be wise in responding to various sciences that develop in Islamic scientific discourse, can synergize and support each other in the realm of understanding the Qur'anic interpretation.